Investigação das propriedades fotofísicas de porfirinas meso substituídas com complexos de RuII e estudo da interação com biomoléculas - Menezes, Lucas Brandalise (2019)
The objective of this work was to investigate the photophysical properties of two porphyrins whose syntheses are already reported in the literature: meso-tetra(4-pyridyl)porphyrin tetra-ruthenated free-base (H2RuTPyP) and meso-tetra(4-pyridyl)porphyrin tetra-ruthenated zinc(II) (ZnRuTPyP). For this, both porphyrins were synthesized according to the Araki and co-workers methodology and properly characterized by elemental analysis, mass spectrometry, ultraviolet-visible, infrared and emission spectroscopy. In addition, solution aggregation assays were performed, photostability studies and singlet oxygen generation were investigated by UV-vis spectroscopy. Moreover, the interactive studies with DNA and HSA were performed via UV-vis spectroscopy, fluorescence emission and theoretical calculations by molecular docking. ZnII-porphyrin (ZnRuTPyP) presented better values for intrinsic DNA binding constant (Kb), and Stern-Volmer quenching constant (KSV), suggesting that both tetra-ruthenated porphyrins interact with major groove and are governed by electrostatic interactions, which is evidenced by molecular docking calculations.